THE CORRELATION BETWEEN SANITARY HYGIENE AND THE PRESENCE OF BACTERIA SUCH AS Escherichia coli AND Salmonella sp. IN BRANDED AND UNBRANDED BOBA DRINKS IN MALANG CITY - Siti Maysaroh; Rr Eko Susetyarini; Fendy Hardian Permana (Fakultas Sains dan Teknologi, Universitas Islam As-Syafi'iyah, 2023)
Boba drink is a variant of a drink that is currently popular in Malang City. Boba drinks have the potential to be a source of disease transmission such as diarrhea if the presentation, storage, and processing of drinks do not apply proper hygiene and sanitation. Escherichia coli and Salmonella sp. is a pathogenic bacterium that can cause diarrhea because it can enter the human body.. The purpose of this study was to analyze the correlation between sanitary hygiene and the presence of bacteria such as Escherichia coli and Salmonella sp., in branded and unbranded boba drinks in Malang City. The research method employed is observational using a quantitative research approach, and the sample strategy is Cluster Random Sampling. The Product Moment correlation test were used to analyse the data. The presence of bacteria Escherichia coli and Salmonella sp., was discovered in unbranded boba drinks in Malang City. The results of the statistical tests show that there is a significant correlation between sanitation hygiene variables and the presence of bacteria such as Escherichia coli and Salmonella sp., in branded and unbranded boba drinks in Malang City. Based on the research obtained, in order for boba drinks consumed to be free from bacterial contamination, further tests need to be carried out on the correct and qualified processing of boba drinks.